Low pressure CVD growth of 2D PdSe2 thin film and its application in PdSe2-MoSe2 vertical heterostructure. (1st April 2022) - Withanage, Sajeevi S; Khondaker, Saiful I
Abstract: Palladium diselenide (PdSe2 ) is a novel member of the transition metal dichalcogenide family with layer dependent bandgap in the infrared regime with potential applications in many electronic and optoelectronic devices. Low pressure chemical vapor deposition (LPCVD) could be an effective way to synthesize large area 2D PdSe2 materials at low growth temperatures creating new opportunities for the widescale applications of PdSe2 . Here, we report LPCVD growth of PdSe2 for the first time at a growth temperature down to 250 °C, which is significantly lower than what was previously reported. The 2 nm Pd films became 8 nm PdSe2 after selenization in the temperature range of 250 °C–375 °C and no thickness variation with growth temperature was observed in our atomic force microscopy study. Raman study showed narrowing of PdSe2 related peaks with increasing growth temperature suggesting improved structural quality of the films. X-ray photoelectron spectroscopy study confirmed complete selenization of the thin films to the lowest growth temperature of 250 °C. Electrical transport properties study showed resistance of the devices decrease with increasing growth temperature possibly due to the improvement of crystallinity. We also found that the devices show p-type behavior with mobilities up to 1 cm 2 V −1 s −1 . The good electrical quality of the film was further confirmed by demonstrating its application in fabricating PdSe2 /MoSe2 vertical heterojunction which showed rectification behavior with a rectification ratio of up to 232. Kelvin probe force microscopy confirmed that the rectification behavior was originated from the work function difference of 0.76 eV between MoSe2 and PdSe2 .